IMU, ICM, Medals, Prizes, and Laureates - Agarwal, Ravi P. (MDPI, 2025)
The book begins with the formal establishment of the International Mathematical Union (IMU) and its purpose of promoting international cooperation in mathematics by supporting and assisting the international Congress of Mathematicians (ICM) every four years. The book presents the most important features of each ICM (from 1897 to 2022) including the history of various medals and awards, particularly the Fields Medal, which is regarded as one of the highest honors a mathematician can receive and has been described as the Nobel Prize of mathematics. For each Laureate, the book provides their family background, a short description of the work that led to the award, a history of academic jobs, research conducted after receiving the award, and a list of further honors and awards. This book will stimulate all mathematicians, especially students who think that mathematics is less rewarding compared to other disciplines.